Do Prisoners Mentalize Differently? Investigating Attachment and Reflective Functioning in a Sample of Incarcerated Lebanese Men - Abi-Habib, Rudy (2020)
Insecure attachment and deficits in mentalizing have been consistently found to be correlated with increased delinquency, conduct disorder and antisocial behaviors. This has been explained by a distancing from the other’s needs and feelings or by an incapacity to consider the effects of one’s behaviors on others. The current study is the first to investigate the association between attachment and mentalizing in a sample of 172 incarcerated Lebanese men, between the ages of 19 and 65, looking for predictors of regret towards the crime committed. Results suggested a significant correlation between insecure attachment and lower mentalizing capacities in our sample. Furthermore, deficits in mentalization, more specifically hypomentalizing strategies, were found to predict a lack of regret towards the crime committed. Findings are discussed within the attachment and mentalization framework, considering cross-cultural influences, guiding future intervention and prevention programs within Lebanese prisons and at-risk groups.